Healthcare Administration 2015
DOI: 10.4018/978-1-4666-6339-8.ch035
|View full text |Cite
|
Sign up to set email alerts
|

Use of Mobile Applications for Hospital Discharge Letters

Abstract: Handover of patient care is a time of particular risk and it is important that accurate and relevant information is clearly communicated. The hospital discharge letter is an important part of handover. However, the quality of hospital discharge letters is variable and letters frequently omit important information. The Cork Letter-Writing Assessment Scale (CLAS) checklist is an itemized checklist developed to improve the quality of discharge letters. The CLAS checklist, with an inbuilt scoring system, is availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“… Completeness and timeliness of hospital discharge communication. Risk of delay Risk of lack of information Maher, Ireland (2013) [ 50 ] Use of mobile applications for hospital discharge letters - improving handover at point of practice. Experimental study (involving fourth-year medical students) ( N = 80).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Completeness and timeliness of hospital discharge communication. Risk of delay Risk of lack of information Maher, Ireland (2013) [ 50 ] Use of mobile applications for hospital discharge letters - improving handover at point of practice. Experimental study (involving fourth-year medical students) ( N = 80).…”
Section: Resultsmentioning
confidence: 99%
“…It might be also useful for young doctors to use checklists or other structured procedures to improve writing [ 4 ]. Maher et al showed that the use of a checklist enhanced the quality (content, structure, and clarity) of medical discharge letters written by medical students [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mobile devices provide many new opportunities and tools for patient care. 3 , 4 An EHR-connected application, for example, can provide the needed task list at timely moments, with real-time documentation. Also, entering data directly on the device could reduce potential transcriptions errors as well as delays in the availability of collected data.…”
Section: Introductionmentioning
confidence: 99%